Ultrafast Track Robotic-Assisted Minimally Invasive Coronary Artery Surgical Revascularization. Issue 5 (September 2017) - Tarola, Christopher L.; Al-Amodi, Hussein A.; Balasubramanian, Sankar; Fox, Stephanie A.; Harle, Christopher C.; Iglesias, Ivan; Sridhar, Kumar; Teefy, Patrick J.; Chu, Michael W.A.; Kiaii, Bob B.
Abstract : Objective: Contemporary anesthetic techniques have enabled shorter sedation and early extubation in off-pump and minimally invasive coronary artery bypass (CABG) surgery. Robotic-assisted CABG represents the optimal surgical approach for ultrafast track anesthesia, with patients able to bypass the cardiac surgical intensive care unit with recovery in the postanesthesia care unit (PACU) and inpatient ward. Methods: In-hospital postoperative outcomes from ninety patients who underwent either elective or urgent robotically-assisted CABG at our institution were reviewed. These patients were carefully selected by a multidisciplinary team to undergo fast-track anesthesia: extubation in the operating room, 4-hour recovery in the postanesthesia care unit and transfer to the inpatient ward. Intrathecal, paravertebral local, and patient-controlled anesthesia techniques were used to facilitate transition to oral analgesics. Results: Average patient age was 61 ± 9 years. Sixty-six patients (73%) were male. Seventy cases were elective, and 20 patients required urgent revascularization. All patients underwent intraoperative angiography after graft construction, which revealed Fitzgibbon class A grafts. There were no in-hospital mortalities. One patient required re-exploration for bleeding, through the same minimally invasive incision, did not require conversion to sternotomy for bleeding, and was transferred to the intensive care unit postexploration for bleeding for standard postoperative care. Postoperative complications were limited to one superficial wound infection. The mean hospital length of stay was 3.5 ± 1.17 days. Conclusions: In patients undergoing robotic-assisted CABG, ultrafast-track cardiac surgery with immediate postprocedure extubation and transfer to the inpatient ward has been demonstrated to be safe with no increase in perioperative morbidity or mortality. It requires a dedicated heart team with a carefully selected group of patients. Avoiding cardiac surgical intensive care unit expedites recovery, with possible avoidance of infection and early discharge from hospital.